Chemical states of PVD-ZrS2 film underneath scaled high-k film with self-oxidized ZrO2 film as interfacial layer. (1st April 2023) - Otomo, Masaki; Hamada, Masaya; Ono, Ryo; Muneta, Iriya; Kakushima, Kuniyuki; Tsutsui, Kazuo; Wakabayashi, Hitoshi
Abstract: Zirconium disulfide (ZrS2 )—an attractive next-generation channel material because of its high mobility—is stabilized in the air by a zirconium dioxide (ZrO2 ) film which functions as a high-k film in MISFET. We fabricated high-k/PVD-ZrS2 stacks with a self-oxidized ZrO2 film as an interfacial layer; their chemical properties were analyzed to clarify how each fabrication process affects the ZrS2 under the oxide film. The results clarified that sulfur vapor annealing (SVA) is critical for fabricating high-quality physical vapor deposition (PVD) ZrS2 films and that the change in surface potential of the ZrS2 films due to interface dipoles between the high-k and Zr-compound films is suppressed with scaling of high-k thickness. The SVA with high-k films also prevents degradation of crystallinity and stoichiometry, enhancing the quality of the ZrS2 films without affecting their surface potential. These achievements enable us to control the threshold voltage in ZrS2 MISFETs.